Company finance in Europe - Samuels, J. M.; Groves, R. E. V.; Goddard, Christopher Scott (London : Institute of Chartered Accountants in England and Wales, 1975)
One of the goals of this book is the compilation under one cover of the basic material for a comparative review of how companies in a number of European countries finance themselves. The book continually compare and contrasts these with the method employed in the UK, and attempts to draw conclusions relating both to the past and to the possible future path of company finance.
Includes bibliographical references and index.
hza 02/08/2018
Loans
Keywords: Corporations; Stock exchanges; Banks and banking